Technology and homology: for a Marxian use of Rossi-Landi in the neo-workerist analysis of the current bio-cognitive capitalism - D’Urso, Andrea (Rivista Italiana di Filosofia del Linguaggio, 2023)
Our contribution aims at reconsidering Ferruccio Rossi-Landi’s pioneering semiotic theory of language as work and trade, based on the homology between material production and linguistic production, compared to the developments of the current mode of production, defined as bio-cognitive capitalism by some neo-workerists. Our study is divided into three parts. The first shows the character of the double up-to-dateness of Rossi-Landian reflection, both with respect to the dominant linguistic theories at the time of its conception and in relation to those that it still allows to criticize in the present, thus proving the effectiveness of the dialectical-materialist method in front of past and present forms of linguistic idealism. The second part refutes the hasty and mystifying attempts to consider Rossi-Landi as outdated through asserted but unproven theses, which are linked to a markedly philosophical workerism recovering pre-Marxian and even pre-Hegelian conceptions, thus ignoring Rossi-Landi’s far-sighted indications. Prolonging them beyond what he himself could do and restarting from Capital, the third part proposes a critique of his concept of linguistic surplus value and its extension into ideological surplus value that allows to complete the homology of the production of commodity-messages, for a Marxian use of Rossi-Landi in the neo-workerist economic analysis